The role and challenges of learning the yellow bible lessons towards students' charles during the Covid-19 pandemic at MA NU TBS Kudus - Muhammad Khoirun Nadlif; Ashif Az Zafi (Universitas Islam Nahdlatul Ulama Jepara, 2021)
During this COVID 19 pandemic, at MA NU Kudus whose daily behavior when learning is not a few students who are late for school, don't do assignments, don't care about the material being taught, often sleep during online learning, often say dirty, often smoke and others. The purpose of this study was to determine the role and challenges of learning the yellow book of Sufism on students' morals during the pandemic at MA NU TBS Kudus. This research method is a qualitative research using a descriptive approach. Data collection techniques in this study used 3 techniques, namely interview, observation, and documentation techniques. Sufism learning during the pandemic at MA NU TBS Kudus has an important role in shaping students' commendable morals, among others, to lead and help students to really remember God by filling their hearts with the word thoyyibah and the sentence of dhikr. While the challenge of learning Sufism during this pandemic is the impact of technology globally, students using technology such as cellphones are not appropriate. So the cellphone should be used for learning, but instead it is made for playing games.